EFEKTIVITAS KAHOOT DALAM PEMBELAJARAN KANJI PADA MAHASISWA ANGKATAN 2021 PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Sulistiowati, Nadia Adam; Basri, Merri Silvia; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The research aims to determine the effectiveness of Kahoot in learning kanji for students the class 2021 of the Japanese Language Education Study Program, FKIP, Riau University. In this study, researchers conducted research to find out wheather there was a significant difference in the reading comprehension ability of kanji students in class of 2021 before and after using learning media in the form of Kahoot. The type of research used is pre-experiment with a One Group Pretest-Posttest Design pattern. The sample in this study consisted of 35 Japanese Language Education students class of 2021. The learning materials used for the pretest, treatment and posttestwere taken from the kanji lecturer manual, namely the どんどんつながる漢字練習帳book. The results of the research can be concluded that the Kahoot learning media iseffective as a kanji learning media.Keywords: Kahoot Media, Kanji, Experiment